Dinamika Problem dan Tantangan Guru Bimbingan dan Konseling di MANU Putri Buntet Pesantren - winda, winda; Sapari, Sapari; Mustofa Abbas, Faiz; BakhriL Amin, M. Saiful; Shofiyah, Zulaehatus (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2025)
This study aims to examine the dynamics of the role, problems, and strategies developed by BK teachers in facing challenges in schools located in Islamic boarding schools, especially in MANU Putri Buntet Pesantren. Using a qualitative approach and case study method, data were obtained through interviews, field observations, and documentation. The data analysis technique used was the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that BK teachers face various internal and external problems, including limited facilities and infrastructure, negative perceptions of BK services, and gaps between counseling approaches and traditional Islamic boarding school values. In responding to these challenges, BK teachers develop collaborative strategies, Islamic value-based approaches, and service method innovations. These findings emphasize the importance of strengthening the role of BK teachers in the context of Islamic boarding schools to create counseling services that are culturally, spiritually, and academically relevant. This study provides conceptual and practical contributions to the development of BK service models based on values ​​and local contexts.